Use of acute hospital beds does not increase as the population ages: results from a seven year cohort study in Germany. Issue 4 (1st April 2002) - Busse, R; Krauth, C; Schwartz, F W
Abstract : Objectives: (1) To compare the number of hospital days used by survivors with those by persons in their last, second last, and third last year of life in relation to age; (2) to analyse lifelong hospital utilisation in relation to life expectancy. Design: Cohort study using a 10% sample (stratified by age and sex) of persons insured by one sickness fund. Setting: Germany, 1989–1995. Subjects: 69 847 survivors (with a minimum of three more years to live), 1385 persons in last, 1368 in second last, and 1333 in third last year of life. Results: The number of days spent in hospital in the last year of life was lowest for the young (24.2 days under age 25) and the old (23.2 days at age 85+) and was greatest at ages 55–64 (40.6 days). The ratio of days to survivors was highest at age 35–44 (31.0) and fell continously thereafter to 4.3 at age 85+. Similar patterns were seen for hospital days in the second and third year before death, except that peaks were at 35–44 years (22.5 and 13.7 days respectively). Calculated lifelong number of hospital days increased with age from 54.8 (death at age 20) to 201.0 (age 90). Numbers of hospital days per year of life, averaged over the entire lifespan, were stable at 2.0–2.2 for deaths between age 50 and 90 (and up to 2.7 at age 20). Conclusions: Lifelong hospital utilisation for persons who die at 50 or later is directly proportional to the number of years lived. These data contradict results from cross sectional studies that suggest an exponential rise in health care costs as longevity increases. They have important implications for projections of future health care expenditure.